Comparative analysis of oil, water, and solid separation performance using a three-phase decanter in palm oil mills: Case study at PKS A and B - M. Sabri; Geubrina Hikmah Sabri (Prosiding SNTTM, 2025)
This study examines the performance of a three-phase decanter centrifuge in separating oil, water, and solids in palm oil mills. Efficient separation is critical to improving crude palm oil (CPO) yield and minimizing losses, yet many mills face challenges such as excessive sludge, unstable emulsions, and oil loss. The objective of this research is to compare the operational performance of decanters at A and B mills and to identify the dominant factors influencing oil loss. A case study approach was employed, combining sampling of light, heavy, and solid phases with operational data analysis and direct observations. The results indicate that PKS A experienced high non-oil solids (NOS) in the feed, which caused excessive oil loss in the sludge, while PKS B faced unstable and high emulsion levels, resulting in greater oil loss in the heavy phase. These findings confirm that decanter performance is highly site-specific, even when identical machines are used. The study concludes that operational strategies must be tailored: reducing NOS in PKS A and controlling emulsions in PKS B. The main contribution of this research is providing empirical evidence of differing decanter challenges across mills, offering practical guidance for optimization. The limitation lies in the scope restricted to two mills, suggesting that future research should include more sites and external variables to develop a comprehensive optimization model.